Embeddedness, social networks and micro and small enterprises dynamics in African informal urban economy - (:unkn) unknown (My University, 2010)
Against a backdrop of rapid urbanization, the issues surrounding the informal economy are particularly crucial in sub-Saharan Africa. Understanding the social regulations governing informal activities is therefore essential. This thesis aims to identify and analyze the nature, origin and influence of social networks on the dynamics and performances of micro and small enterprises in the informal economy of Bobo-Dioulasso (Burkina Faso). It is based on a multidisciplinary research approach. Theoretical reflection is first conducted on the concepts of embeddedness and social networks. This was followed by the adoption of a micro-socio-economic analysis framework geared towards the study of micro-entrepreneurs' personal networks of access to resources. Empirically, our work is based on an original survey conducted between 2006 and 2008. The information gathered (quantitative and qualitative) enables us to describe the configuration of the social network of micro-entrepreneurs in its many dimensions, to apprehend certain dynamic aspects and to assess its impact on business performances. The analysis combines a comprehensive approach, multidimensional statistics and econometrics. It reveals the complexity of the relationship formation process during entrepreneurial trajectories. It also highlights the importance of network professionalization, as well as strong ties and the social and professional proximity of its members. Four types of network are identified, each with a specific impact on firms' performances.
Keywords: African Research